Inherent variability in growth and development of two ecotypes of sesame plant (Sesamum sp.) in Malaysia - Tan, Shee Pei; Mohamad, Rosli; Puteh, Adam; Morshed, Md. Mahbub (Universiti Putra Malaysia Press, 2015)
Differences in the growth and development of sesame ecotypes growing sporadically as uncultivated plant in dissimilar agro-ecological and habitat conditions of Serdang and Port Dickson of Malaysia have not been studied. The purpose of the study was to compare the inherent variations in growth parameters and degree of relationships between the two ecotypes over time. The quantitative growth parameters of the plants’ height, leaf number per plant, total leaf area, fresh and dry weight of leaves, fresh and dry weight of roots were measured at 2, 4, 8 and 12 weeks after planting under the same growing conditions. Results indicated that the two ecotypes manifested almost similar growth patterns and the variations on growth parameters between the ecotypes were statistically insignificant. Regression analysis showed that all the growth parameters increased exponentially over time, and the growth parameters were positively correlated between the ecotypes. Thus, this study suggested that a high homology in the growth patterns between the two sesame ecotype could exist when grown under the same growing conditions, although both have adapted to different habitat conditions.